TOTAL QUALITY MANAGEMENT (TQM) MODEL FOR MALAYSIAN CONSTRUCTION ORGANIZATIONS - MOHD GHANI, SITI NOFARAHHANIM (2021)
Construction industry is one of the most important industries that have big impact and highly contributes to the world’s economy, but it is also commonly known as an industry that has significant issues with quality of material, workmanship, and building.